The The Role of Financial Audit Institution (LPK) and Financial Accountability of Provincial and Regency Council of Scout Movement throughout Bali - Diputra, I Gede Aristana; Admadja, Anantawikrama Tungga; Purnamawati, I Gusti Ayu (Ekuitas: Jurnal Pendidikan Ekonomi, 2023)
This study aims to investigate the extent of Financial Audit Institution (LPK) role in supervising, examining, and implementing financial management accountability within the Provincial and Regency Council of the Scout Movement throughout Bali. The method administered was descriptive research with a qualitative approach. Data analysis went through stages, namely: data collection, data reduction, data display, and conclusion drawing/verification. The results of the research show that: 1) The primary source of income for council was from the government; 2) LPK had been formed but had not been fully formed based on the Memorandum of Association/Articles of Association (AD/ART), it was necessary to improve the composition, qualifications and increase the members’ independence; 3) The significance of LPK was not optimal as there were no technical guidelines and implementation instructions related to financial audits issued by the National Council; 4) LPK was not paid, in other words working based on the concept of "ngayah" or voluntarily; 5) The LPK that had worked and carried out inspections and issued an Audit Report (LHP) is the LPK of Buleleng Regency Council with the scope of the examination not only on Financial Aspects, but includes examination on Functions, Human Resources, Infrastructure and Work Methods Aspects; 6) Council had implemented procedural accountability, process accountability, vertical accountability and horizontal accountability; 7) Council was expected to be able to optimize the role of LPK in the financial audit process and optimize the Council Business Entity to increase revenue from internal sources.